2022
DOI: 10.3390/app12031672
|View full text |Cite
|
Sign up to set email alerts
|

Phobia Exposure Therapy Using Virtual and Augmented Reality: A Systematic Review

Abstract: A specific phobia is a common anxiety-related disorder that can be treated efficiently using different therapies including exposure therapy or cognitive therapy. One of the most famous methods to treat a specific phobia is exposure therapy. Exposure therapy involves exposing the target patient to the anxiety source or its context without the intention to cause any danger. One promising track of research lies in VR exposure therapy (VRET) and/or AR exposure therapy (ARET), where gradual exposure to a negative s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(27 citation statements)
references
References 50 publications
1
23
0
3
Order By: Relevance
“…Amongst healthcare students, virtual reality interventions have been observed to improve skill competencies, and better appreciation of symptom and illness [ 62 ]. Earlier studies have found that AR/VR interventions can be adopted to manage conditions such as specific phobias, autism spectrum disorder, psychotic conditions, substance related disorders, depression and eating disorders [ 23 , 24 , 63 , 64 ]. In our review, we observed that VR intervention could help to assess and enhance medication adherence amongst patients with schizophrenia (Baker et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Amongst healthcare students, virtual reality interventions have been observed to improve skill competencies, and better appreciation of symptom and illness [ 62 ]. Earlier studies have found that AR/VR interventions can be adopted to manage conditions such as specific phobias, autism spectrum disorder, psychotic conditions, substance related disorders, depression and eating disorders [ 23 , 24 , 63 , 64 ]. In our review, we observed that VR intervention could help to assess and enhance medication adherence amongst patients with schizophrenia (Baker et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Since then, the use of VR as a treatment modality has grown. Of note, there are recent studies examining the effectiveness of AR/VR-based therapeutic modalities in the management of patients with neurodevelopmental spectrum conditions (such as autism spectrum disorders, attention deficit hyperactivity disorders) [ 20 , 21 , 22 , 23 ], anxiety disorders (such as phobias) [ 24 , 25 , 26 , 27 ], obsessive compulsive disorder [ 28 , 29 , 30 ], post-traumatic stress disorder [ 31 ], and cognitive impairments in the elderly [ 32 , 33 ]. In comparison, there are fewer studies specifically elucidating the effectiveness of AR/VR based interventions as a psychoeducational tool such as in improving understanding of mental illnesses, engendering more positive attitudes regarding people with mental illnesses [ 34 , 35 ] and reduction of stigma [ 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Beyond basic neural mechanisms of balance control, our findings further suggest that VR may be useful for therapeutic purposes. For example, VR exposure therapy has been presented as a promising concept for managing phobias and anxieties, such as towards heights or flying, by gradually exposing patients to a negative stimulus ( Rothbaum et al, 1997 ; Krijn et al, 2004 ; Bush, 2008 ; Albakri et al, 2022 ). There is already research in this area suggesting benefits in terms of fear of falling and fall risk in older adults ( Rendon et al, 2012 ; Levy et al, 2016 ), and clinically in people with acrophobia ( Coelho et al, 2009 ; Rimer et al, 2021 ), or anxiety disorders ( Meyerbröker and Emmelkamp, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, virtual reality exposure has also proven promising (68)(69)(70). Efficacy was also demonstrated for augmented reality exposure, a similar tech-based approach, for many other specific phobias (71). Moreover, case reports have shown individuum-level success for approaches like selfexposure (67), individualization of therapy (72), cognitive restructuring (73), and applied tension (74).…”
Section: Dsm-5 Criteria Of Specific Phobia (30029)mentioning
confidence: 99%